PD-1 and TIGIT coexpression identifies a circulating CD8 T cell subset predictive of response to anti-PD-1 therapy. Issue 2 (13th November 2020) - Simon, Sylvain; Voillet, Valentin; Vignard, Virginie; Wu, Zhong; Dabrowski, Camille; Jouand, Nicolas; Beauvais, Tiffany; Khammari, Amir; Braudeau, Cécile; Josien, Régis; Adotevi, Olivier; Laheurte, Caroline; et al.
Abstract : Background: Clinical benefit from programmed cell death 1 receptor (PD-1) inhibitors relies on reinvigoration of endogenous antitumor immunity. Nonetheless, robust immunological markers, based on circulating immune cell subsets associated with therapeutic efficacy are yet to be validated. Methods: We isolated peripheral blood mononuclear cell from three independent cohorts of melanoma and Merkel cell carcinoma patients treated with PD-1 inhibitor, at baseline and longitudinally after therapy. Using multiparameter flow cytometry and cell sorting, we isolated four subsets of CD8 + T cells, based on PD-1 and TIGIT expression profiles. We performed phenotypic characterization, T cell receptor sequencing, targeted transcriptomic analysis and antitumor reactivity assays to thoroughly characterize each of these subsets. Results: We documented that the frequency of circulating PD-1 + TIGIT + (DPOS) CD8 + T-cells after 1 month of anti-PD-1 therapy was associated with clinical response and overall survival. This DPOS T-cell population was enriched in highly activated T-cells, tumor-specific and emerging T-cell clonotypes and T lymphocytes overexpressing CXCR5, a key marker of the CD8 cytotoxic follicular T cell population. Additionally, transcriptomic profiling defined a specific gene signature for this population as well as the overexpression of specific pathways associated with the therapeutic response. Conclusions: Our results provide a convincing rationale for monitoring this PD-1 + TIGIT + circulating population as an early cellular-based marker of therapeutic response to anti-PD-1 therapy.